Автотематизм у структурі поетики мемуарно-автобіографічного циклу Уласа Самчука - Цехмейструк, М. (Літературознавчі обрії. Праці молодих учених, 2010)
In the given article the four interrelated books by Ulas Samchuk «On the White Horse», «On the Black Horse», «Five past Twelve» and «Planet DP» are considered through the category of the author’s self-topicality. The author’s «I» and deep philosophical evaluations of his discourse are studied in the indirect dialogue of the author with the cynical destruction of the person’s inner world by the totalitarian system.